Evaluating the Bank of Canada staff economic projections using a new database of real-time data and forecasts - Julien Champagne; Guillaume-Poulin Bellisle; Rodrigo Sekkel (Bank of Canada, 2018)
We present a novel database of real-time data and forecasts from the Bank of Canada's staff economic projections. We then provide a forecast evaluation for GDP growth and CPI inflation since 1982: we compare the staff forecasts with those from commonly used time-series models estimated with real-time data and with forecasts from other professional forecasters and provide standard bias tests. Finally, we study changes in the predictability of the Canadian economy following the announcement of the inflationtargeting regime in 1991. Our database is unprecedented outside the United States, and our evidence is particularly interesting, as it includes over 30 years of staff forecasts, two severe recessions and different monetary policy regimes. The database will be made available publicly and updated annually.
Keywords: C32; E17; E37; 330; Monetary policy; Economic models; Inflation targets; Econometric and statistical methods